E-Sedekah Ethics: Unraveling Virtual Altruism & Distribution Disparity in Rahman's Framework - Lasmi Anisa Putri Lasmi; Duski Samad; Firdaus, ST. Mamad (Institute of Research and Community Service Universitas Islam Negeri Mahmud Yunus Batusangkar, 2025)
Amidst the increasingly massive phenomenon of digital philanthropy, E-Sedekah emerges as a promising innovation to reach a wider range of donors and mobilize charitable funds efficiently. However, its implementation also presents significant ethical challenges, particularly concerning the concept of virtual altruism, meaning virtual kindness that is often superficial and lacks deep-rooted empathy, as well as the problem of uneven wealth distribution, which potentially widens the gap of social inequality. This research is motivated by the urgency to critically examine E-Sedekah practices from the social justice perspective of Fazlur Rahman, a prominent modernist Islamic thinker who emphasizes the contextual interpretation of the Qur'an as a foundation for addressing socio-economic disparities. The aim is not only to critique existing E-Sedekah practices but also to highlight the implications of virtual altruism on the sustainability of charity, and to identify fair and transformative distribution strategies to maximize positive impact for beneficiaries. Employing a qualitative method involving in-depth content analysis and hermeneutics of Fazlur Rahman's works, along with primary and secondary data from E-Sedekah platforms in Indonesia, the study's comprehensive results indicate that while E-Sedekah holds immense potential as a philanthropic instrument, fundamental reforms are necessary to ensure its accountability, transparency, and distribution effectiveness in accordance with Islamic principles. The recommendations include the development of a comprehensive digital ethics framework based on maqasid syariah for optimizing the role of ZISWAF in building social justice in the digital era